Generalized lymphatic anomaly in a pediatric patient manifesting as a rare presentation of hemorrhagic pleural effusion: a case report - Xuehong Zhang; Jiuling Wang; Shouxing Duan; Yongping Yan; Libin Wang (BMC Pediatrics)
Abstract Background Generalized lymphatic anomaly (GLA) is a rare congenital lymphatic malformation (LM) characterized by multiple infiltrating lymphangiomas in various tissues. Owing to its rarity, information on this disease is obtained mainly through case reports, leading to delayed diagnosis. In this study, we reported a case of generalized lymphatic anomaly in a pediatric patient manifesting as hemorrhagic pleural effusion. Case presentation A 6-year-old female presented with abdominal pain, shortness of breath, chronic cough with yellow sputum production, and diminished respiration accompanied by pleural effusion. Imaging revealed significant left-sided pleural effusion with mediastinal involvement, left lung atelectasis, and multiple cystic lesions in both liver and spleen. Thoracoscopic exploration was conducted in response to her active intrathoracic bleeding, which identified a persistently hemorrhagic mass in the left mediastinum. The mass in the left mediastinum was removed, and pathological examination confirmed hyperplasia and expansion of the papillary endothelial cells within the lymphatic vessels. After intensive anti-infection therapy and symptomatic and supportive treatment, the patient’s condition improved significantly. The regular outpatient follow-ups were continued until July 2024. Subsequent positron emission tomography (PET)CT at another hospital revealed multiple skeletal lesions in the limbs. Following treatment with sirolimus, no recurrence of pleural effusion was observed, and the patient’s condition remained stable. Conclusion In patients with generalized lymphatic anomalies (GLAs), involvement of the thoracic cavity may lead to hemorrhagic pleural effusion, thereby broadening the landscape of GLA phenotypic presentations. Furthermore, this case highlights the importance of complete radiological evaluation of susceptible patients with GLA to avoid diagnostic delay in this morbid condition. We also review recently discovered genetic changes underlying lymphatic anomaly development and the progress of treatment.